2009
DOI: 10.1080/15228860802594615
|View full text |Cite
|
Sign up to set email alerts
|

Pollination, Fertilization and Floral Traits Co-Segregating with Autofertility in Faba Bean

Abstract: Heterotic autofertility in faba bean has been investigated in cultivars, inbred lines and F 1 populations but not in segregating generations. This study evaluated the association between autofertility and floral components in the presence of different levels of heterosis in segregating generations, derived from two inbred linesautofertile line Kristall 25 (K25) and autosterile line Diana 07 (D07). The autofertile populations had fewer pollen grains, greaterstyle-ovary angle, longer style, lower papillae densit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 24 publications
3
18
0
Order By: Relevance
“…In our study, Hedin/2, an inbred line reputed to be highly autofertile, had no measurable dependence on additional pollination and as discussed below, the pollination treatments actually reduced productive output. There are several heritable traits associated with autofertility relating to the quantity and quality of pollen per flower, angles of the petals and floral organs, and characteristics of the stigma 34,35 . While the highest yields in our study came from commercial cultivars receiving additional pollination treatments ( Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, Hedin/2, an inbred line reputed to be highly autofertile, had no measurable dependence on additional pollination and as discussed below, the pollination treatments actually reduced productive output. There are several heritable traits associated with autofertility relating to the quantity and quality of pollen per flower, angles of the petals and floral organs, and characteristics of the stigma 34,35 . While the highest yields in our study came from commercial cultivars receiving additional pollination treatments ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Alongside heritable autofertility described above, high levels of autofertility are seen in hybrid faba bean plants, which are typically also capable of greater yield production 25,36 . The number of hybrid plants in a given faba bean population is typically around 35% 37 but this can change depending on the levels of www.nature.com/scientificreports www.nature.com/scientificreports/ cross fertilization in previous generations 34 . Random differences in the proportion of hybrid individuals in each sample of experimental plants may partially explain the high variability within and between some of our treatment combinations.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, Cao et al (2017) found that several potential regulators are implicated in the vernalization process in faba bean. Faba bean is a self-pollinated plant with significant levels of cross-pollination ( Suso et al, 1996 ; Chen, 2009 ). The main pollinating insects are honeybees ( Apis spp.)…”
Section: Morphological Description and Botanical Characterizationmentioning
confidence: 99%
“…Therefore, heat stress at a given time point could damage some flowers while others remain undamaged through differences in the timing of their development, providing a source of fertile pollen. In a typical faba bean crop, a proportion of pollination is by spontaneous auto-fertilization, while the remainder requires an insect visit ( e.g., Chen, 2009 ). Following heat stress however, all flowers with damaged pollen would effectively be male-sterile and unable to self-pollinate ( Drayner, 1959 ).…”
Section: Introductionmentioning
confidence: 99%